Earthworm (Oligochaeta: Lumbricidae) fauna from Pirin Macedonia (southwestern Bulgaria) - Valchovski, Hristo (Macedonian Journal of Ecology and Environment, 2016)
The paper deals with contribution of the knowledge of earthworm fauna from Pirin Macedonia (Southwestern Bulgaria). During investigations eight earthworm taxa were registered. Two lumbricids Aporrectodea longa (Ude, 1885) and Lumbricus terrestris Linnaeus, 1758 are registered for the first time in Pirin Macedonia . In this paper we summarized our and previous published data for diversity of earthworms and established the list for the entire territory of the explored region. The list provide information about distribution and zoogeographical position of earthworms in Pirin Macedonia (Southwestern Bulgaria).